Co3O4/Fe0.33Co0.66P Interface Nanowire for Enhancing Water Oxidation Catalysis at High Current Density. Issue 45 (25th September 2018) - Zhang, Xiaoyan; Li, Jing; Yang, Yong; Zhang, Shan; Zhu, Haishuang; Zhu, Xiaoqing; Xing, Huanhuan; Zhang, Yelong; Huang, Bolong; Guo, Shaojun; Wang, Erkang
Abstract: Designing well‐defined nanointerfaces is of prime importance to enhance the activity of nanoelectrocatalysts for different catalytic reactions. However, studies on non‐noble‐metal‐interface electrocatalysts with extremely high activity and superior stability at high current density still remains a great challenge. Herein, a class of Co3 O4 /Fe0.33 Co0.66 P interface nanowires is rationally designed for boosting oxygen evolution reaction (OER) catalysis at high current density by partial chemical etching of Co(CO3 )0.5 (OH)·0.11H2 O (Co‐CHH) nanowires with Fe(CN)6 3−, followed by low‐temperature phosphorization treatment. The resulting Co3 O4 /Fe0.33 Co0.66 P interface nanowires exhibit very high OER catalytic performance with an overpotential of only 215 mV at a current density of 50 mA cm −2 and a Tafel slope of 59.8 mV dec −1 in 1.0m KOH. In particular, Co3 O4 /Fe0.33 Co0.66 P exhibits an obvious advantage in enhancing oxygen evolution at high current density by showing an overpotential of merely 291 mV at 800 mA cm −2, much lower than that of RuO2 (446 mV). Co3 O4 /Fe0.33 Co0.66 P is remarkably stable for the OER with negligible current loss under overpotentials of 200 and 240 mV for 150 h. Theoretical calculations reveal that Co3 O4 /Fe0.33 Co0.66 P is more favorable for the OER since the electrochemical catalytic oxygen evolution barrier is optimally lowered by the active Co‐ and O‐sites from the Co3 O4 /Fe0.33 Co0.66 P interface. Abstract : Co3 O4 /Fe0.33 Co0.66 P interface nanowires are rationally designed and synthesized by a universal strategy of partial chemical etching of Co(CO3 )0.5 (OH)·0.11H2 O nanowires with Fe(CN)6 3−, followed by low‐temperature phosphorization with NaH2 PO2 ·H2 O for boosting oxygen evolution.